Financial performance of Islamic banks and conventional banks in Malaysia: A comparative study - Nor Baayah, Idris (2014)
This paper has analyzed and compared the financial performance of Islamic banks and conventional banks in Malaysia. This study is useful for depositors, bank managers, shareholders, investors, regulators and researchers in order to provide a true picture of Islamic banks and conventional banks financial condition. Study has been conducted in term of profitability, liquidity, risk and solvency and efficiency for five years period from 2008 to 2012. Study was taken only for five years period due to some of Islamic banks chosen was just started the operation e.g. CIMB Islamic (2003), Maybank Islamic (2008) and AmIslamic (2006). Data had been generated from income statement, balance sheet and notes to the accounts of the banks’ annual reports. The sources of banks’ annual reports are from the websites of the banks and also Bloomberg. This study had selected six Islamic banks and six conventional banks established in Malaysia, which includes Bank Islam (M) Berhad, Bank Muamalat (M) Berhad, Bank Kerjasama Rakyat (M) Berhad, Maybank Islamic Berhad, CIMB Islamic Bank Berhad, AmIslamic Bank Berhad, Affin Bank Berhad, CIMB Bank Berhad, Malayan Banking Berhad, Ambank (M) Berhad, HSBC Bank (M) Berhad and Hong Leong Bank Berhad. The list of conventional banks and Islamic banks is obtained from Bank Negara Malaysia’s (BNM) website. The significant of data has been determined using independent sample t-test and one-way ANOVA analysis. Study has concluded that Islamic banks are less profitable, less liquid, more risky but more efficient in managing the operating expenses to generate revenue as compared conventional banks.